HJURP is recruited to double-strand break sites and facilitates DNA repair by promoting chromatin reorganization - Serafim, Rodolfo B. [UNESP]; Cardoso, Cibele; Storti, Camila B.; da Silva, Patrick; Qi, Hongyun; Parasuram, Ramya; Navegante, Geovana [UNESP]; Peron, Jean Pierre S.; Silva, Wilson A.; Espreafico, Enilza M.; Paçó-Larson, Maria L.; Price, Brendan D.; et al. (Springer Nature, 2024)
HJURP is overexpressed in several cancer types and strongly correlates with patient survival. However, the mechanistic basis underlying the association of HJURP with cancer aggressiveness is not well understood. HJURP promotes the loading of the histone H3 variant, CENP-A, at the centromeric chromatin, epigenetically defining the centromeres and supporting proper chromosome segregation. In addition, HJURP is associated with DNA repair but its function in this process is still scarcely explored. Here, we demonstrate that HJURP is recruited to DSBs through a mechanism requiring chromatin PARylation and promotes epigenetic alterations that favor the execution of DNA repair. Incorporation of HJURP at DSBs promotes turnover of H3K9me3 and HP1, facilitating DNA damage signaling and DSB repair. Moreover, HJURP overexpression in glioma cell lines also affected global structure of heterochromatin independently of DNA damage induction, promoting genome-wide reorganization and assisting DNA damage response. HJURP overexpression therefore extensively alters DNA damage signaling and DSB repair, and also increases radioresistance of glioma cells. Importantly, HJURP expression levels in tumors are also associated with poor response of patients to radiation. Thus, our results enlarge the understanding of HJURP involvement in DNA repair and highlight it as a promising target for the development of adjuvant therapies that sensitize tumor cells to irradiation.